2018
DOI: 10.25134/erjee.v7i1.1497
|View full text |Cite
|
Sign up to set email alerts
|

Cello as a Language Teaching Method in Industrial Revolution 4.0 Era

Abstract: CELLO is derived from Community English Language Learning and Orai. It is a new teaching method developed especially in the community of English language learning based on the idea of Curran�s work on teaching method. CELLO is a combination between an innovative teaching method and media technology called Orai Application that is applied in teaching and learning of speaking especially in fostering students� fluency. Today, all graduates face a world transformed by technology, in which the Internet, cloud compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…The next technology review is the integration of Orai application reported by Halimah et al (2018). From this research, it can be implied that Orai application can help students' in developing their speaking skills regarding to their Volume 5 Number 2, May 2020 pronunciation, and energy level.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The next technology review is the integration of Orai application reported by Halimah et al (2018). From this research, it can be implied that Orai application can help students' in developing their speaking skills regarding to their Volume 5 Number 2, May 2020 pronunciation, and energy level.…”
Section: Discussionmentioning
confidence: 91%
“…As Simon-Lewis (2017) stated that Orai helps us in choosing words and give feedback to the filler words, pacing and word clarity (wired.co.uk). Moreover, Halimah et al (2018) also pointed out that learning to speak using the application makes students feel less anxious and it also promotes self-study during learning process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 20-item informal likert scale for answering second research question, and 9-item informal likert scale for answering second research question were created by the researchers. The data was elicited through five options which ranged from 1 -Strongly disagree to 5 -Strongly agree (Dörnyei, 2003) in (Halimah, Ibrahim, & Lustyantie, 2019). The participants were instructed to choose one of the choices reflecting their thoughts.…”
Section: Methodsmentioning
confidence: 99%
“…There are some previous studies in line with this study. The first study was done by [13]. Her paper entitled "CELLO as a Language Teaching Method in Industrial Revolution Era" published in English Review: Journal of English Education.…”
Section: A Previous Studiesmentioning
confidence: 99%